Identifying Change Blindness Among University Students - Ahmed, Maryam Alaa; Majeed, Azhar Mohammed (Journal of Posthumanism, 2025)
The present study aims to investigate the level of change blindness among university students. The sample consisted of 400 male and female students from the University of Baghdad across various academic disciplines. A change blindness test was administered to the participants. The results revealed the presence of change blindness among the students, with no statistically significant differences observed between males and females or between students of scientific and humanities disciplines.